A meta analysis of the skeletal and dental effects of fixed functional appliances treatment - Hamed, Taher (My University, 2006)
SABİT FONKSİYONEL AYGITLARLA TEDAVİNİN İSKELETSEL VE DENTAL ETKİLERİNİN META ANALİZİ Bu sistematik taramanın amacı, sabit fonksiyonel aygıtların iskeletsel ve dental etkilerinin değerlendirilmesidir. Bu çalışmada kullanılan tüm makaleler, bilgisayardan MEDLINE literature taraması ile

dergilerden (1966 dan Eylül 2005 e kadar) belirlenmiştir. ‘Ortodonti’ terimi başlık olarak taranmış ve tarama ‘sabit fonksiyonel aygıtlar’, ‘mandibular retrognati’, ‘jusper jumper’, ‘bite correcter’, ‘herbst apareyi’ terimleri ile combine edilmiştir. Medline taraması ile belirlenmiş 3068 çalışma arasından 49 makale konu ile ilgili bulunmuş fakat sadece 32 tanesi seçim kriterlerine uymuştur. Bu çalışmaların 23 tanesinde sabit fonksiyonel tedavi süresince braket yerleştirilmemiş, diğer 6 çalışmada braketler sabit fonksiyonel aygıt ile birlikte uygulanmıştır. Meta analizine gore sabit fonksiyonel aygıtların kısa dönem etkileri şıunlardır: 1) Yatay yöndeki çeneler arası ilişkideki düzelme esas olarak alt çenenin büyümesine bağlıdır. 2) Alt çene düzlem açısı, ortalamaya bakıldığında tedaviden etkilenmemiştir. 3) Yatay yöndeki keser ve molar ilişkideki düzelme iskeletsel ve dental değişimlere sonucu elde edilmiştir. SUMMARY The aim of this systematic review was to evaluate the skeletal and dental effect of the fixed functional appliances. All articles used in this study have been identified by computerized MEDLINE literature search (from 1966 through September 2005) of English written journals. The term “orthodontics” has been searched in the subject heading and it was crossed with various combination of the following terms fixed functional appliance mandibular retrognathism, jusper jumper, bite corrector, Herbst appliance. Among 3068 studies which were identified by Medline search, 49 articles were related to the review topic, but only 29 of them met the selection criteria. In 23 of these studies brackets were not placed during the treatment with fixed functional appliances however, in the other 6 studies brackets were placed along with fixed functional appliances. Our study was conducted only on the 23 articles and this because in other 6 articles treatment methods used were different. Based on Meta analysis, the short-term effect of fixed functional appliances showed that (1) the improvement of the sagittal jaw relationship was mainly due to increased mandibular length. (2) Mandibular plane angle was on the average unaffected by treatment. (3) Improvement in sagittal incisor and molar relationships was achieved by skeletal and dental changes.
Keywords: Diş ve Diş Hastalıkları; Ortodonti_Tedavi